Seasonal variations of schizophrenic patients in emergency departments in Sofia, Bulgaria - Zornitsa Spasova (South Eastern European Journal of Public Health, 2015)
Aim: The purpose of this study was to reveal the seasonal distribution of emergency department visits of schizophrenic patients in Sofia, Bulgaria.